Analisis Dialek Pada Tokoh Asal Korea Pengguna Bahasa Indonesia - Reni Rohaeni; Sarah Gina Azzahra; Denis Taftazani Akbar (Asosiasi Periset Bahasa Sastra Indonesia, 2023)
The background to this research was carried out by the researcher's curiosity regarding the dialect phenomenon that arises when speakers of their mother tongue (Korean) speak Indonesian. The purpose of this research is so that readers can find out and describe what dialect is, how phonology influences language dialect, and the results of dialect analysis on characters from Korea who use Indonesian, including Instagram celebrities and content creators who are the object of this research. The method used by researchers is a qualitative descriptive method. Meanwhile, the data sources in this research are YouTube videos and Tiktok content. This research was carried out by analyzing the pronunciation of words and how they were pronounced by Korean characters who could speak Indonesian. Based on the results of the analysis, the researcher found that phonology is one of the influencing factors in producing dialect when speaking and the researcher was also able to conclude that the use of descriptive methods with a qualitative approach was suitable for application in this research. It is hoped that this research will be useful for readers so that readers gain more knowledge about phonology and dialect.